THE HISTORY OF DEVELOPMENT OF POTTERY AND ITS PLACE IN APPLIED ART - Shahzoda, Jumayeva; Kholbazarvich, Qudratov Javlon (PT. Antis International Publisher, 2024)
This article contains a lot of scientific information about the history of the development of pottery and its role in practical art